1990
DOI: 10.1096/fasebj.4.5.2155149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of GABA A receptors

Abstract: The major type of receptor for the inhibitory neurotransmitter gamma-aminobutyric acid (GABA), called the GABAA receptor, is a member of a gene superfamily of ligand-gated ion channels. This receptor is a hetero-oligomeric protein composed of several distinct polypeptide types (alpha, beta, gamma, and delta). Molecular cloning of these polypeptides reveals that they show 20-40% identity with each other, and 10-20% identity with polypeptides of the nicotinic acetylcholine receptors and strychnine-sensitive glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
412
0
19

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 956 publications
(432 citation statements)
references
References 59 publications
1
412
0
19
Order By: Relevance
“…In the adult central nervous system (CNS), γ-amino butyric acid (GABA) is a predominant neurotransmitter which is synaptically released, mediates fast inhibitory synaptic transmission, and regulates excitatory activity of neurons (Olsen and Tobin, 1990;Macdonald and Olsen, 1994). Recent studies have revealed that GABA serves as an excitatory transmitter during brain development, and induces trophic responses, such as regulation of cell proliferation, cell migration, axonal growth, synapse formation, steroid-mediated sexual differentiation and cell death (Varju et al, 2001;Ben-Ari, 2002;McCarthy et al, 2002;Owens and Kriegstein, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the adult central nervous system (CNS), γ-amino butyric acid (GABA) is a predominant neurotransmitter which is synaptically released, mediates fast inhibitory synaptic transmission, and regulates excitatory activity of neurons (Olsen and Tobin, 1990;Macdonald and Olsen, 1994). Recent studies have revealed that GABA serves as an excitatory transmitter during brain development, and induces trophic responses, such as regulation of cell proliferation, cell migration, axonal growth, synapse formation, steroid-mediated sexual differentiation and cell death (Varju et al, 2001;Ben-Ari, 2002;McCarthy et al, 2002;Owens and Kriegstein, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular cloning studies revealed five different but homologous receptor subunits (a,/3, y, 6, and p), each of which exists in the brain in different variants. Additional diversity arises from RNA splicing [35,36,46,52,71]. In recombinant expression studies, the association of different cloned subunit variants leads to functional diversity of the GABA A receptor complexes with respect to conductance and gating properties of the chloride channels, the allosteric modulation by benzodiazepines and the sensitivity for agonists.…”
Section: Introductionmentioning
confidence: 99%
“…In recombinant expression studies, the association of different cloned subunit variants leads to functional diversity of the GABA A receptor complexes with respect to conductance and gating properties of the chloride channels, the allosteric modulation by benzodiazepines and the sensitivity for agonists. The type of a subunit, in combination with a /3 and a y2 subunit, is a major determinant of the type of benzodiazepine pharmacology displayed [13,35,39,52,[57][58][59]72]. The GABAAR affinity and efficacy for benzodiazepines is also influenced by the ,/ subunit present, with receptors containing a 72 subunit exibiting the classical benzodiazepine modulation [59,63,76].…”
Section: Introductionmentioning
confidence: 99%
“…In the adult central nervous system (CNS), γ-amino butyric acid (GABA) mediates fast inhibitory synaptic transmission and regulates the excitatory activity of neurons (Olsen and Tobin, 1990;Macdonald and Olsen, 1994). In the immature CNS, on the other hand, GABA is an excitatory transmitter and is involved in controlling morphogenesis (Ben-Ari, 2002;McCarthy et al, 2002;Owens and Kriegstein, 2002;Represa and Ben-Ari, 2005).…”
mentioning
confidence: 99%